(untitled) (Alternautas, 2022)
At the beginning of July 2020, in Ecuador, as in most of the countries of the region, started loosening emergency lockdown restrictions designed to tackle COVID-19 pandemic. In Ecuador, the governmental discourse drew upon the illustrative figure of colours in the traffic lights: high-risk zones depicted as red; the colour yellow to denote control over the pandemic and green delineating lower risk zones. Initially, Ecuador was one of the countries with the highest incidence of COVID-19 in Latin America but with the progressive expansion of the pandemic in the region, other countries such as Brazil, Peru and Chile overtook Ecuador in terms of incidences of COVID per 100,000 people, whilst United States became the country where the virus spread the most.